2008
DOI: 10.1097/qco.0b013e3282f4f237
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis: new findings in the pathogenesis and treatment of this disease

Abstract: The possible link between gastroesophageal reflux and nontuberculous mycobacterial lung disease, and the microbiology and resistance patterns of bacteria observed in these patients were clarified. A large study of inhaled tobramycin for exacerbations was inconclusive, but macrolide therapy and hyperosmolar agents hold promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
2
22
0
1
Order By: Relevance
“…Our study confirms IPV's cardiovascular safety in patients with bronchiectasis. Similar to the study by Van Ginderdeuren et al, 22 we observed no change in S pO 2 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study confirms IPV's cardiovascular safety in patients with bronchiectasis. Similar to the study by Van Ginderdeuren et al, 22 we observed no change in S pO 2 .…”
Section: Discussionsupporting
confidence: 81%
“…Bronchiectasis is usually associated with chronic cough, increasing secretions, and recurrent airway and pulmonary infections that might result in loss of lung function and lead to early death. 2 The goals of bronchiecDrs Paneroni, Simonelli, Bianchi, and Vitacca are affiliated with Servizio di Riabilitazione Cardio-Respiratoria, Salvatore Maugeri Foundation, Istituto di Ricovero e Cura a Carattere Scientifico, Institute of Lumezzane, Lumezzane, Italy. Drs Clini and Degli Antoni are affiliated with the University of Modena, and with L'unità Operativa di Pneumologia e Riabilitazione Respiratoria, Ospedale Privato Accreditato Villa Pineta, Gaiato, Italy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspiration event can produce lung irritation and subsequent infl ammation. Recurrent LPR with aspiration may manifest itself with many different pulmonary problems, such as refractory asthma, 6 ground-glass infi ltrates, 13 interstitial lung disease, 14 bronchiectasis, 15,16 and aspiration pneumonitis. 17 Although it is important to use well-established GI studies to document and elucidate specifi c pathophysiologic problems, false-positives and false-negatives may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the inflammation can lead to bronchiectasis characterized by permanent dilation of the airway and thickening of the bronchial wall. Because of these changes, areas like this can function as a seedbed for future infections (Bilton, 2008;Ilowite et al, 2008;Javidan-Nejad & Bhalla, 2009;King, 2009;Goeminne & Dupont, 2010). Recurring infections are thought to be the main reason why, in time, these patients develop a decrease in lung function.…”
Section: Clinical Aspectsmentioning
confidence: 99%